Review on cross‐layer design for cognitive ad‐hoc and sensor network. Issue 6 (1st April 2020) - Singhal, Chetna; Rajesh, A.
Abstract : Most of the ad‐hoc networks including wireless sensor network operates in unlicensed spectrum bands (e.g. 2.4 GHz ISM band), which is shared by other wireless technologies. This leads to coexistent interference and degrades the performance of ad‐hoc sensor network (AHSN). Introducing cognitive radio (CR) concept in AHSN, the unutilised licensed spectrum (white spaces) can be used opportunistically without disturbing licensed holders. Conventional TCP/IP layered architecture for CR network lacks in mobility, data transfer performance, energy efficiency, quality of service and so on. Coupling of some of the layers allows coordination, interaction and joint optimisation of protocols to achieve significant performance improvements for CR‐AHSN. Of late, many researches are going on different approaches of using CR for reusing unused spectrum and enhancing total system capacity. This study presents a comprehensive review of various cross‐layer design approaches in CR sensor network.